Enhanced performance of CoFe2O4 supercapacitors through synergistic interaction of Co2+ and Fe2+ - Ghazal, Aqsa; Mendhe, Avinash C.; Kore, Ashish; Dhas, Suprimkumar; Batool, Rabia; Kim, Daewon (Elsevier BV, 2024)
Hybrid supercapacitors incorporating multivalent ions have emerged as innovative electrochemical energy storage systems due to their high energy and power densities. Despite their promising attributes, the full potential of these devices remains unexplored because of the complex electrochemical interactions of multivalent ions within electrode materials, which impede widespread adoption in hybrid supercapacitors. A thorough investigation is conducted into the long-term electrochemical behavior of CoFe2O4 electrodes in the presence of multivalent ions (Co2+/Co3+ and Fe2+/Fe3+ transitions) and K+ ion electrolytes. The correlation of the electrochemical behavior with detailed analyses of elemental composition, surface and structural morphology, and the electronic structure evolution of the CoFe2O4 heterostructures, in contrast to pristine Fe2O3 and Co3O4 electrodes, is examined. The CoFe2O4 electrode possesses a high specific surface area and porosity, facilitating greater electrolyte penetration and an increase in electroactive sites, achieving a high specific capacitance of 1231 F/g at 10 mA/cm2 compared to Co3O4 and Fe2O3. This is attributed to its transformation into nanoflakes and nanosheet morphology, which promotes efficient K+ ion intercalation and deintercalation. A symmetric supercapacitor configured with CoFe2O4 electrodes achieves 230 F/g at 10 mA/cm2, signifying an energy density of 25.88 Wh/kg and a power density of 281.25 W/kg, with 90.9 % capacitance retention across 5000 cycles. Furthermore, an asymmetric supercapacitor integrated with AC and CoFe2O4 electrodes achieves the highest energy density of 39.76 Wh/kg while maintaining 96.6 % of its initial capacity after 5000 cycles. The improved performances of the electrodes are well matched with the first principle-based density functional theory (DFT) outcomes. This research advances the understanding of multivalent ion charge storage mechanisms, offering critical insights for enhancing hybrid supercapacitor performance.